Cyclodextrin‐Based [c2]Daisy Chain Rotaxane Insulating Two Diarylacetylene Cores. Issue 6 (9th December 2020) - Tsuda, Susumu; Komai, Yoshitsugu; Fujiwara, Shin‐ichi; Nishiyama, Yutaka
Abstract: A [c2]daisy chain rotaxane with two diarylacetylene cores was efficiently synthesized in 53 % yield by capping a C2 ‐symmetric pseudo[2]rotaxane composed of two diarylacetylene‐substituted permethylated α‐cyclodextrins (PM α‐CDs) with aniline stoppers. The maximum absorption wavelength of the [c2]daisy chain rotaxane remained almost unchanged in various solvents, unlike that of the stoppered monomer, indicating that the two independent diarylacetylene cores were insulated from the external environment by the PM α‐CDs. Furthermore, the [c2]daisy chain rotaxane exhibited fluorescence emission derived from both diarylacetylene monomers and the excimer, which implies that the [c2]daisy chain structure can undergo contraction and extension. This is the first demonstration of a system in which excimer formation between two π‐conjugated molecules within an isolated space can be controlled by the unique motion of a [c2]daisy chain rotaxane. Abstract : A [c2]daisy chain rotaxane, in which two independent diarylacetylene cores are insulated by two permethylated α‐cyclodextrins (PM α‐CDs), is efficiently synthesized using the Janus [2]rotaxane strategy. The observation of both monomer and excimer emission in various solvents reveals that frequent shuttling of the rotaxane subunits occurs in solution.